The Moldovan Social Investment Fund : Building Local Capacity and Improving Services - Bezhanyan, Anush; Ionascu, Alexei (World Bank, Washington, DC, 2012)
The note reviews the impact of the Moldova Social Investment Fund (MSIF), aimed at building local capacity, and improving services, though also looks at the implementation problems connected with community participation. To address these issues the MSIF management delegated responsibilities to implementing agencies, while also improved technical assistance. The development of partnerships achieved greater impact, which led to performance contracts, as tools to promote the sustainability of investments. Lessons reinforce the need for community ownership, and, suggest wider community consultation to identify, and solve technical issues. The need to maintain links with communities after subproject implementation is emphasized, to ensure long-term sustainability.